Scone Island : an Ike Schwartz mystery - Ramsay, Frederick (Ramsay, Frederick. Ike Schwartz mystery., 2012)
When sheriff and former CIA agent Ike Schwartz and his fiancée, Ruth Dennis, vacation on Scone Island, a small piece of land off the coast of Maine with no electricity or phone service, Ike's CIA past comes back to haunt them.